(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2013)
The study was carried out during 2007-2008 season in the research field of Wheat Research Centre, Bangladesh Agricultural Research Institute, Dinajpur to know the effect of lime, Magnesium (Mg) and Boron (B) on yield and yield components of wheat and also their residual effect on mungbean. The geographical position of the area is between 25°62´ N, 88°63´ E and 38.20 meter above sea level. The experiment was laid out in Randomized Complete Block Design with three replications, both in wheat and mungbean. Treatments for wheat were (I) recommended fertilizer + Mg + B, (II) recommended fertilizer + lime + B + Mg, (III) recommended fertilizer + lime + Mg, (IV) recommended fertilizer + lime + B and (V) control (Only recommended fertilizer) and for mungbean were (I) recommended fertilizer + Mg + B, (II) 75% of recommended dose, (III) recommended fertilizer + B, (IV) recommended fertilizer + Mg and (V) control (without fertilizers). Results showed that the highest yield and yield components of wheat were recorded from recommended fertilizers + lime + B + Mg treated plot and the second highest were recorded from recommended fertilizers + lime + Mg treated plot. The lowest was recorded in control plot (only recommended fertilized). In case of mungbean the highest was found from recommended fertilizers + B treated plot, this treatment was limed in previously cultivated wheat crop and the lowest was recorded from control plot (without fertilizer). DOI: http://dx.doi.org/10.3329/ijarit.v1i1-2.13923 Int. J. Agril. Res. Innov. & Tech. 1 (1&2): 9-15, December, 2011